(untitled) (Archive of Conferences, 2020)
In connection with the Mongol conquest, the scientific, cultural, socio-economic spheres of life of the peoples of Maverannahr fell into decay. Despite this, during the reign of one of the Chagatai khans, Kebek Khan, trade, construction flourished, and sciences developed. Thanks to his wisdom and exactingness, he made a certain contribution to the development of the region. In connection with the great attention with which the local population from ancient times treated science and education, culture, representatives of the educated strata have always tried to lead the people out of the difficult situations.